FDA orphan drug designations for lysosomal storage disorders: a cross-sectional analysis - Garbade, Sven; Zielonka, Matthias; Mechler, Konstantin; Kölker, Stefan; Hoffmann, Georg F.; Staufner, Christian; Mengel, Eugen; Ries, Markus (PLOS ONE, 2020)
Purpose - To provide a quantitative clinical-regulatory insight into the status of FDA orphan drug designations for compounds intended to treat lysosomal storage disorders (LSDs). - - Methods - Assessment of the drug pipeline through analysis of the FDA database for orphan drug designations with descriptive and comparative statistics. - - Results - Between 1983 and 2019, 124 orphan drug designations were granted by the FDA for compounds intended to treat 28 lysosomal storage diseases. Orphan drug designations focused on Gaucher disease (N = 16), Pompe disease (N = 16), Fabry disease (N = 10), MPS II (N = 10), MPS I (N = 9), and MPS IIIA (N = 9), and included enzyme replacement therapies, gene therapies, and small molecules, and others. Twenty-three orphan drugs were approved for the treatment of 11 LSDs. Gaucher disease (N = 6), cystinosis (N = 5), Pompe disease (N = 3), and Fabry disease (N = 2) had multiple approvals, CLN2, LAL-D, MPS I, II, IVA, VI, and VII one approval each. This is an increase of nine more approved drugs and four more treatable LSDs (CLN2, MPS VII, LAL-D, and MPS IVA) since 2013. Mean time between orphan drug designation and FDA approval was 89.7 SD 55.00 (range 8-203, N = 23) months. - - Conclusions - The drug development pipeline for LSDs is growing and evolving, with increased focus on diverse small-molecule targets and gene therapy. CLN2 was the first and only LSD with an approved therapy directly targeted to the brain. Newly approved products included “me-too”-enzymes and innovative compounds such as the first pharmacological chaperone for the treatment of Fabry disease.
Gesehen am 02.07.2020